The operational role of remote sensing in forest and landscape management: Focus group discussion proceedings - Takao, G.; Priyadi, H.; Ikbal Nursal, W (Center for International Forestry Research, 2010)
Remote Sensing has contributed to forest and landscape management. The technology, which includes sensors, processing software and analysis, has been extensively studied and applied. Studies that employed remote sensing have improved understanding of the sites studied. At the strategic level of forest planning, or in general planning for forest resource allocation over a wide area, remote sensing can play an important role in estimating and monitoring forest cover. At the tactical level, however, when planning forest management activities in a specific forested landscape, remote sensing has not yet contributed as much as expected: Methods proved successful under research conditions cannot always be applied to operational management. There is a gap between scientific and operational uses. Recognising this gap, forest management practitioners and scientists gathered for a daylong focus group discussion to examine constraints and understand better what practitioners expected remote sensing to do for them. The following recommendations arose from the group discussions.